Implementation and application of functional languages : 24th International Symposium, IFL 2012, Oxford, UK, August 30 - September 1, 2012, Revised Selected Papers (Lecture Notes in Computer Science, 2013)
This book contains the selected peer-reviewed and revised papers from the 24th International Symposium on Implementation and Application of Functional Languages, IFL 2012, held in Oxford, UK, in August/September 2012. The 14 papers included in this volume were carefully reviewed and selected from 28 revised submissions received from originally 37 presentations at the conference. The papers relate to the implementation and application of functional languages and function-based programming.